TUMOR RELATED EPILEPSY - CASE REPORT AND LITERATURE REVIEW AND COMPARISON - Marcelina Kurek,; Justyna Małyska,; Aleksandra Wiśniewska,; Karolina Kasprzak,; Małgorzata Kuczek,; Stanisław Kasprzak,; Sebastian Turek,; Aleksandra Franczuk, (International Journal of Innovative Technologies in Social Science, 2025)
Tumor-related epilepsy is a recognized entity in pediatric neurology, most often linked to low-grade epilepsy-associated tumors (LEATs). We report the case of a 13-year-old girl presenting with two generalized tonic-clonic seizures, after which MRI revealed a small right occipital/parietal cortical lesion, radiologically suggestive of a low-grade glial tumor, most consistent with ganglioglioma. The patient developed obesity, depressive disorder with suicide attempt, and self-harming behaviors, which complicated her clinical course. Despite antiepileptic therapy, seizure control remained suboptimal due to irregular medication use. Neurosurgical evaluation recommended resection after further imaging with neuronavigation, but surgery was postponed. This case highlights the challenges of managing epilepsy associated with extratemporal LEATs and underscores the importance of a multidisciplinary approach that includes neurology, neurosurgery, psychiatry, and oncology to address both neurological and psychosocial outcomes. The literature case reports comparison highligts the different symptoms, treatment methods and treatment outcomes of treatment of tumor related epilepsy. It is important to perform imagining after seziures occured.